Early detection of metabolic changes using microdialysis during and after experimental kidney transplantation in a porcine model - Fonouni, Hamidreza; Esmaeilzadeh, Majid; Jarahian, Parvin; Tahmasbi Rad, Morva; Golriz, Mohammad; Faridar, Alireza; Hafezi, Mohammadreza; Jafarieh, Shadi; Kashfi, Arash; Yazdi, Seid Hashem Fani; Soleimani, Mehrdad; Longerich, Thomas; et al. (Surgical innovation, 2011)
Background: Microdialysis (MD) can detect organ-related metabolic changes before they become measurable in plasma through the biochemical parameters. This study aims to evaluate the early detection of metabolic changes during experimental kidney transplantation (KTx). Material and methods: During preparation of 8 donor kidneys, one MD catheter was inserted in the renal cortex and samples were collected. After a 6-hour cold ischemia time (CIT), kidneys were implanted in the 8 recipient pigs. Throughout the warm ischemia time (WIT) and after reperfusion, kidneys were monitored. The interstitial glucose, lactate, pyruvate, glutamate, and glycerol concentrations were evaluated. Results: A significant decline in glucose level was observed at the end of CIT. The lactate level was reduced to the minimum point of 0.35 ± 0.08 mmol/L in CIT. After reperfusion, lactate values raised significantly. During the WIT, the pyruvate level increased, continued until the end of the WIT. For glutamate, a steady increase was noted during explantation, CIT, WIT, and early reperfusion phases. The increase of glycerol value continued in the early postreperfusion, which was then followed by a sharp decline. Conclusion: MD is a fast and simple minimally invasive method for measurement of metabolic substrates in renal parenchyma during KTx. MD offers the option of detecting minor changes of interstitial glucose, lactate, pyruvate, glutamate, and glycerol in every stage of KTx. Through the use of MD, metabolic changes can be continuously monitored during the entire procedure of KTx.